Ca2+ signals: The versatile decoders of environmental cues. (March 2013) - Sarwat, Maryam; Ahmad, Parvaiz; Nabi, Gowher; Hu, Xiangyang
<x xml:space="preserve">Abstract</x> Plants are often subjected to various environmental stresses that lead to deleterious effects on growth, production, sustainability, etc. The information of the incoming stress is read by the plants through the mechanism of signal transduction. The plant Ca2+ serves as secondary messenger during adaptations to stressful conditions and developmental processes. A plethora of Ca2+ sensors and decoders functions to bring about these changes. The cellular concentrations of Ca2+, their subcellular localization, and the specific interaction affinities of Ca2+ decoder proteins all work together to make this process a complex but synchronized signaling network. In this review, we focus on the versatility of these sensors and decoders in the model plant Arabidopsis as well as plants of economical importance. Here, we have also thrown light on the possible mechanism of action of these important components.